PENGARUH DESAIN PRODUK DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN PADA MARKET PLACE SHOPEE - Febrianti, Nur Lia; Islamuddin, Islamuddin (UM. Bengkulu, 2025)
This study aims to determine the effect of product design on purchasing decisions for Ventela brand shoe customers in Bengkulu City. To determine the effect of Online Customer Rating on Purchasing Decisions for Ventela brand shoe customers in Bengkulu City. To find out the influence between Product Design and Online Customer Rating on Purchasing Decisions for Ventela brand shoe customers in Bengkulu City. This type of research is research using a quantitative approach.